#### Answer

-2

#### Work Step by Step

From the graph we see that $f(4)=2$ and $f(2)=-2$, so:
$(f\circ f)(4)=f(f(4))=f(2)=-2$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

-2

From the graph we see that $f(4)=2$ and $f(2)=-2$, so:
$(f\circ f)(4)=f(f(4))=f(2)=-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.